HOLOCENE ERUPTIVE HISTORY OF SHIVELUCH VOLCANO, KAMCHATKA PENINSULA, RUSSIA - Ponomareva V.; Kyle P.; Pevzner M.; Sulerzhitsky L.; Hartman M. (My University, 2007)
The Holocene eruptive history of Shiveluch volcano, Kamchatka Peninsula, has been reconstructed using geologic mapping, tephrochronology, radiocarbon dating, XRF and microprobe analyses. Eruptions of Shiveluch during the Holocene have occurred with irregular repose times alternating between periods of explosive activity and dome growth. The most intense volcanism, with frequent large and moderate eruptions occurred around 6500–6400 BC, 2250–2000 BC, and 50–650 AD, coincides with the all-Kamchatka peaks of volcanic activity. The current active period started around 900 BC; since then the large and moderate eruptions has been following each other in 50–400 yrs-long intervals. This persistent strong activity can be matched only by the early Holocene one.Most Shiveluch eruptions during the Holocene produced medium-K, hornblendebearing andesitic material characterized by high MgO (2.3–6.8 wt %), Cr (47–520 ppm), Ni (18–106 ppm) and Sr (471–615 ppm), and low Y (> 18 ppm). Only two mafic tephras erupted about 6500 and 2000 BC, each within the period of most intense activity.Many past eruptions from Shiveluch were larger and far more hazardous then the historical ones. The largest Holocene eruption occurred ∼1050 AD and yielded >2.5 km3 of tephra. More than 10 debris avalanches took place only in the second half of the Holocene. Extent of Shiveluch tephra falls exceeded 350 km; travel distance of pyroclastic density currents was > 22 km, and that of the debris avalanches ≤20 km.
Keywords: 38.37.25 Вулканология; Шивелуч